Crystal–Glass High‐Entropy Nanocomposites with Near Theoretical Compressive Strength and Large Deformability. Issue 34 (19th July 2020) - Wu, Ge; Balachandran, Shanoob; Gault, Baptiste; Xia, Wenzhen; Liu, Chang; Rao, Ziyuan; Wei, Ye; Liu, Shaofei; Lu, Jian; Herbig, Michael; Lu, Wenjun; Dehm, Gerhard; et al.
Abstract: High‐entropy alloys (HEAs) and metallic glasses (MGs) are two material classes based on the massive mixing of multiple‐principal elements. HEAs are single or multiphase crystalline solid solutions with high ductility. MGs with amorphous structure have superior strength but usually poor ductility. Here, the stacking fault energy in the high‐entropy nanotwinned crystalline phase and the glass‐forming‐ability in the MG phase of the same material are controlled, realizing a novel nanocomposite with near theoretical yield strength ( G /24, where G is the shear modulus of a material) and homogeneous plastic strain above 45% in compression. The mutually compatible flow behavior of the MG phase and the dislocation flux in the crystals enable homogeneous plastic co‐deformation of the two regions. This crystal–glass high‐entropy nanocomposite design concept provides a new approach to developing advanced materials with an outstanding combination of strength and ductility. Abstract : A novel crystal–glass high‐entropy nanocomposite with near theoretical yield strength and large deformability is achieved by controlling both the stacking fault energy in the high‐entropy nanotwinned crystalline phase and the glass‐forming‐ability in the metallic glass phase. The mutually compatible flow behavior of the glass phase and the dislocation flux in the crystals enable homogeneous plastic co‐deformation of the two regions.